IMPLEMENTATION OF COOPERATIVE AND CONFRONTATIONAL, CONSTRUCTIVE AND DESTRUCTIVE STRATEGIES IN GERMAN-LANGUAGE MEDIA DURING THE COVID-19 PANDEMIC (BASED ON THE MATERIALS OF THE MAGAZINE "DER SPIEGEL") - Степанова, Татьяна (SWorldJournal, 2021)
The article analyzes implementation of constructive / destructive and cooperative / confrontational strategies in the discourse of the German-language print media in relation to the COVID - 19 problem, compares their use during the first and second waves